Muslim Responses to the Communist Revival in Indonesian Politics - Suhelmi, Ahmad (Studia Islamika, 2007)
The sudden reappearance of Marxist-Communist literature following the downfall of Soeharto's New Order regime was a concerning development for many Muslim groups in Indonesian, especially those in the so-called Aliansi Anti-Komunis (the Anti-communist Alliance, or AAK). Members of the Alliance reacted by burning Leftist books on April 19, 2001 and demanded that all Marxist-Communist literature found in book shops throughout the country be removed over the following days. Some social groups within Indonesia reacted positively to the book burning arguing that it was in accordance with the constitution, while opponents viewed it as anarchic and extreme. This article discusses the AAK's reaction to the purported Communist threat with particular reference to the burning of the leftist literature.DOI: 10.15408/sdi.v14i2.547